Suplementação de citrato de sódio incrementa o desempenho em lutadores de judô - Valido, Charles Nardelli (2014)
Introduction. Metabolic acidosis causes reduced performance in judo and sodium citrate has suggested as a buffering being investigated. Aim. To analyse the effect of sodium citrate oral supplementation (0.5 g.kg-1 of body mass) on the performance of judo contest. Methods. In a double-blind crossover design, 12 highly trained athletes (. purple belt) were select, but only eight completed all stages of this study. Simulation competition was realized (three matches of Five minutes and 15-minute interval) and lactate, blood gases (pH, PCO2, PO2, HCO3- and bases), perceived exertion and score by match was measure. After the third match, fighters performed Judogi Handgrip Test, and the Special Judo Fitness Test (SJFT). Results. After all the matches, lactate level was higherin Citrate group (p<0,05) and perceived exertion was higher in the Control (p<0,05). After the second and third match the supplemented group showed higher blood concentration of HCO3-, pH and lower base deficit (p<0,05). In the third match, the Control group have significantly more penalty number (10 vs. 3; p<0,05). After the simulated competition, the Citrate group showed better performance for maximum dynamic (16,5 }1,7 vs. 12,8 }1,4 rep.; p<0,05) and static force (47,4 }3,9 vs. 39,5 }4,0, sec.; p<0,05), and lower fatigue index in SJFT (13,5 }0,3 vs. 14,6 }0,3; p<0,05). Only one figther shown na adverse effect from the sodium citrate consumption. Conclusion. Prior intake (60 minutes) of sodium citrate results in better physical and competition performance in judo athletes.